Titanium dioxide for high temperature processing of polycarbonate and method of making same
Patent Information
- Application Number
- CN202610960254.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-29
- Publication Date
- 2026-10-09
AI Technical Summary
[0009]发明人认识到,在现有技术的此类方案中,仍存在进一步改进的空间
[0020]根据本发明的实施例的一种用于高温加工聚碳酸酯的钛白及其制备方法中,通过缺陷钝化降低热催化活性,通过梯度致密与互混结构提升高温抗裂性,通过有机锚固实现低吸湿性与高相容性,所得钛白含水量≤0.12%,可在280~320℃下显著抑制聚碳酸酯黄变与力学衰减,适用于光学级、汽车级、电子电器级高端聚碳酸酯材料,制备工艺稳定可控,可直接适配工业化生产线。
Smart Images

Figure CN122878779A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of inorganic pigment modification technology, and in particular to a titanium dioxide for high-temperature processing of polycarbonate and its preparation method. Background Technology
[0002] Polycarbonate is a class of thermoplastic engineering plastics with excellent comprehensive properties, including high light transmittance, high impact strength, excellent dimensional stability, and heat resistance. It is widely used in automotive headlight covers, optical components, electronic and electrical housings, and high-end structural parts. Due to the high rigidity of polycarbonate molecular chains and its high melting temperature, the melt processing temperature typically needs to be controlled within the range of 280–320°C to ensure sufficient melting of the polycarbonate resin, good flow and molding performance, and stable product properties. Within this high-temperature range, the resin system places extremely stringent requirements on the thermal stability, surface activity, interfacial compatibility, and hygroscopicity of the fillers.
[0003] Rutile titanium dioxide is the most widely used white pigment and light stabilizer in polycarbonate, imparting excellent whiteness, hiding power, and long-term weather resistance to the products. However, the direct application of conventional titanium dioxide to high-temperature processing of polycarbonate leads to a series of intractable problems. Firstly, the surface of titanium dioxide particles contains a large number of oxygen vacancies and Ti... 3+ Defects and surface hydroxyl groups exhibit significant thermocatalytic activity at high temperatures, exacerbating the thermo-oxidative degradation of polycarbonate molecular chains. This leads to chain breakage, a decrease in molecular weight, and ultimately, increased yellowing index and reduced impact strength in the finished product. Secondly, traditional titanium dioxide surface modification often employs single-layer or multi-layer stepwise coating processes. These coating layers have distinct phase interfaces and weak interlayer bonding, making them prone to cracking and peeling under high-temperature, high-shear processing conditions. This re-exposes the titanium dioxide surface, further intensifying catalytic degradation. Furthermore, conventional organic modifiers often have insufficient compatibility with the polycarbonate chain structure, causing titanium dioxide particles to easily agglomerate and disperse unevenly in the resin, affecting the material's mechanical stability. Finally, the high number of hydroxyl groups on the surface of ordinary titanium dioxide makes it highly hygroscopic. At high temperatures, moisture exacerbates the hydrolysis and chain scission of polycarbonate, further deteriorating the product's appearance and mechanical properties.
[0004] Currently, most existing technologies employ individual optimization methods such as doping, coating, and modification, or simple combinations of multiple methods, without forming a truly synergistic system. For example, doping with high-valence metals alone easily leads to agglomeration, failing to achieve uniform defect passivation; simply using gradient coating still results in a brittle outer layer prone to cracking. Conventional organic modification involves only physical adsorption or simple covalent bonding, which cannot simultaneously meet the requirements of low moisture absorption, high compatibility, and high-temperature resistance without detachment. Therefore, there is an urgent need for a specialized titanium dioxide that can simultaneously achieve low thermal catalytic activity, high-temperature coating stability, low moisture absorption, and high dispersion compatibility, and provides a preparation method suitable for industrial production.
[0005] Chinese patent application CN103214880A discloses an inorganic coating method for titanium dioxide. This patent employs a zirconium-silicon-aluminum ternary stepwise coating method, applicable to the field of general weather-resistant titanium dioxide.
[0006] Chinese patent application CN107805321A discloses a method for preparing a polycarbonate-specific titanium dioxide pigment. This patent employs conventional stepwise silicon-aluminum coating followed by silane coupling agent treatment to improve dispersion and compatibility.
[0007] Chinese patent application CN114231054A discloses a polycarbonate-specific titanium dioxide and its preparation method. This patent employs zirconium-aluminum inorganic coating combined with conventional organic treatment to improve dispersion and whiteness.
[0008] Chinese patent application CN114634694A discloses a high-temperature resistant, easily processed PC material, its preparation method, and its applications. This patent improves the polycarbonate resin formulation and does not involve the structural design of TiO2-based special pigments.
[0009] The inventors recognized that there was still room for further improvement in such solutions in the prior art. Summary of the Invention
[0010] The main objective of this invention is to provide a titanium dioxide for high-temperature processing of polycarbonate and its preparation method. The invention reduces thermal catalytic activity through defect passivation, improves high-temperature crack resistance through gradient densification and mixed structure, and achieves low hygroscopicity and high compatibility through organic anchoring. The resulting titanium dioxide has a water content of ≤0.12% and can significantly inhibit yellowing and mechanical decay of polycarbonate at 280~320℃. It is suitable for high-end polycarbonate materials of optical, automotive, and electronic grades. The preparation process is stable and controllable and can be directly adapted to industrial production lines. According to one aspect of the present invention, a titanium dioxide for high-temperature processing of polycarbonate is provided, which uses rutile titanium dioxide as a matrix. The matrix surface includes three structural layers from the inside to the outside. The three structural layers include a high-valence metal-zirconium composite defect passivation layer, a zirconium-aluminum-silicon continuous gradient dense layer, and a carbonate-based phosphate dynamic anchoring layer. There are no obvious interfaces between the three structural layers, and they are in a continuous transition state.
[0011] According to one embodiment of the present invention, the high-valence metal-zirconium composite defect passivation layer is composed of one or two of ZrO2 and Sb2O5 and Nb2O5, wherein the mass of ZrO2 is 0.5% to 1.0% of the matrix mass, and the doping amount of the high-valence metal is 0.1% to 0.2% of the matrix mass; zirconium and the high-valence metal form a Zr-OM covalent bond structure (M is Sb or Nb).
[0012] According to one embodiment of the present invention, the zirconium-aluminum-silicon continuous gradient dense layer is an amorphous co-deposition structure, and the total mass is 1.5% to 3.5% of the matrix mass.
[0013] According to one embodiment of the present invention, the zirconium-aluminum-silicon continuous gradient dense layer has a zirconium content that gradually decreases from the inside out, an aluminum content that first increases and then decreases, and a silicon content that gradually increases, with a coating density of 65% to 85% and no abrupt changes in composition between layers.
[0014] According to one embodiment of the present invention, the outermost layer of the zirconium-aluminum-silicon continuous gradient dense layer is an Al2O3-SiO2 blend layer, wherein the mass of the Al2O3-SiO2 blend layer is 0.5% to 1.0% of the matrix mass, wherein Al2O3 accounts for 25% to 35% and SiO2 accounts for 65% to 75%.
[0015] According to one embodiment of the present invention, Al2O3 is uniformly embedded in the amorphous network of silicon oxide in the form of nanocrystals to form a rigid-tough interpenetrating structure.
[0016] According to one embodiment of the present invention, the mass of the carbonate-based phosphate dynamic anchoring layer is 1.0%-2.5% of the matrix mass. One end of the modifier molecule in the carbonate-based phosphate dynamic anchoring layer is bonded to the Al2O3-SiO2 blend layer through the phosphate group, and the other end is molecularly compatible with the polycarbonate chain segment through the carbonate structure, thereby achieving efficient sealing of surface hydroxyl groups and making the finished product water content ≤0.12%.
[0017] According to one embodiment of the present invention, the titanium dioxide has a particle size of 0.20~0.25μm, and the product obtained under processing conditions of 280~320℃ has a yellowing index b value ≤1.2 and a cantilever beam impact strength ≥70kJ / m. 2 .
[0018] According to another aspect of the present invention, a method for preparing titanium dioxide for high-temperature processing of polycarbonate is provided, comprising the following steps: S1. Prepare a slurry with a solid content of 30%~40% by preparing rutile titanium dioxide, add sodium polyacrylate and polyethylene glycol-polypropylene glycol block copolymer as a composite dispersant, adjust the pH to 7.5~9.0, disperse at high speed and then heat to 65~75℃; S2. Add zirconium source solution to the slurry. When the zirconium source is added to 50% of the total amount, mix the high-valence metal source with the zirconium source in proportion and continue to add it. Keep it warm and mature to form a high-valence metal-zirconium composite defect passivation layer. S3. Gradually adjust the dropping rate of the zirconium source and aluminum source to make the system continuously transition from zirconium-rich to aluminum-rich. Then adjust the pH to 7.0~8.0 and adjust the dropping rate of the aluminum source and silicon source to make the system continuously transition from aluminum-rich to silicon-rich, forming a zirconium-aluminum-silicon continuous gradient dense layer. S4. Maintain a high flow rate of silicon source and add it in conjunction with a low flow rate of aluminum source, while adding tetraethyl orthosilicate to promote the formation of the outermost Al2O3-SiO2 blend layer. S5. Wash the slurry until the conductivity is ≤40μS / cm, and filter to obtain filter cake; S6. The filter cake is redispersed, and after heating, carbonate-based phosphate is added. Dynamic anchoring is completed using a three-stage temperature-controlled reaction. S7. After three-stage vacuum drying, inert airflow pulverization, and low-temperature dehumidification, a titanium dioxide product with a moisture content of ≤0.12% is obtained.
[0019] According to one embodiment of the present invention, the high-valence metal source is one or more of Sb2O5 and Nb2O5.
[0020] According to an embodiment of the present invention, a titanium dioxide for high-temperature processing of polycarbonate and its preparation method are described. The thermocatalytic activity is reduced by defect passivation, the high-temperature crack resistance is improved by gradient densification and mixed structure, and the low hygroscopicity and high compatibility are achieved by organic anchoring. The resulting titanium dioxide has a water content of ≤0.12%, and can significantly inhibit the yellowing and mechanical decay of polycarbonate at 280~320℃. It is suitable for high-end polycarbonate materials of optical grade, automotive grade, and electronic and electrical grade. The preparation process is stable and controllable and can be directly adapted to industrial production lines. Attached Figure Description To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some implementation examples of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0021] Figure 1 A schematic diagram of a titanium dioxide for high-temperature processing of polycarbonate is shown according to an exemplary embodiment of the present invention. Detailed Implementation
[0022] The following detailed description of the embodiments is intended to exemplify the principles of the present invention, but should not be construed as limiting the scope of the invention. The present invention can be implemented in many different forms and is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.
[0023] These embodiments are provided to make this disclosure thorough and complete, and to fully express the scope of the invention to those skilled in the art. It should be noted that, unless otherwise specifically stated, the relative arrangement of components and steps, material composition, numerical expressions, and values set forth in these embodiments should be interpreted as merely exemplary and not as limiting.
[0024] It should be noted that, in the description of this invention, unless otherwise stated, "a plurality of" means two or more; the terms "upper," "lower," "left," "right," "inner," and "outer," etc., indicating orientation or positional relationships, are only for the convenience of describing this invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of this invention. When the absolute position of the described object changes, the relative positional relationship may also change accordingly.
[0025] It should also be noted that, in the description of this invention, unless otherwise explicitly specified and limited, the terms "installation," "connection," and "joining" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a direct connection or an indirect connection through an intermediate medium. Those skilled in the art can understand the specific meaning of the above terms in this invention depending on the specific circumstances. When a specific device is described as being located between a first device and a second device, an intermediary device may or may not be present between the specific device and the first or second device.
[0026] All terms used in this invention have the same meaning as understood by one of ordinary skill in the art to which this disclosure pertains, unless otherwise specifically defined. It should also be understood that terms defined in general dictionaries should be interpreted as having meanings consistent with their meanings in the context of the relevant art, and not as idealized or highly formalized, unless expressly defined herein.
[0027] Techniques, methods, and equipment known to those skilled in the art may not be discussed in detail, but where appropriate, such techniques, methods, and equipment should be considered part of the specification.
[0028] like Figure 1 As shown, the present invention provides a titanium dioxide for high-temperature processing of polycarbonate, which uses rutile titanium dioxide as a matrix. The matrix surface includes three structural layers from the inside to the outside. The three structural layers include a high-valence metal-zirconium composite defect passivation layer, a zirconium-aluminum-silicon continuous gradient dense layer, and a carbonate-based phosphate dynamic anchoring layer. There are no obvious interfaces between the three structural layers, and they are in a continuous transition state.
[0029] In the titanium dioxide and its preparation method for high-temperature processing of polycarbonate according to embodiments of the present invention, the thermocatalytic activity is reduced by defect passivation, the high-temperature crack resistance is improved by gradient densification and mixed structure, and the low hygroscopicity and high compatibility are achieved by organic anchoring. The resulting titanium dioxide has a water content of ≤0.12%, and can significantly inhibit the yellowing and mechanical decay of polycarbonate at 280~320℃. It is suitable for high-end polycarbonate materials of optical grade, automotive grade, and electronic and electrical grade. The preparation process is stable and controllable and can be directly adapted to industrial production lines. In some specific embodiments, the high-valence metal-zirconium composite defect passivation layer is composed of ZrO2 and one or two of Sb2O5 and Nb2O5. The mass of ZrO2 is 0.5% to 1.0% of the matrix mass, and the doping amount of the high-valence metal is 0.1% to 0.2% of the matrix mass. Zirconium and the high-valence metal form a Zr-OM covalent bond structure (M is Sb or Nb), which can reduce oxygen vacancies on the titanium dioxide surface and reduce Ti... 3+ Concentration, thereby inhibiting high-temperature thermal catalytic activity.
[0030] Based on the above embodiments, the zirconium-aluminum-silicon continuous gradient dense layer is an amorphous co-deposition structure, with a total mass of 1.5% to 3.5% of the substrate mass.
[0031] In some specific embodiments, the zirconium-aluminum-silicon continuous gradient dense layer gradually decreases in zirconium content from the inside out, increases and then decreases in aluminum content, and gradually increases in silicon content. The coating density gradually increases from 65% to 85%, with no abrupt changes in composition between layers, which can significantly reduce interfacial stress and improve the stability of high-temperature structures.
[0032] Based on the above embodiments, the outermost layer of the zirconium-aluminum-silicon continuous gradient dense layer is an inorganic coated Al2O3-SiO2 blend layer, the mass of which is 0.5% to 1.0% of the matrix mass, wherein Al2O3 accounts for 25% to 35% and SiO2 accounts for 65% to 75%.
[0033] In some specific embodiments, Al2O3 is uniformly embedded in the amorphous network of silicon oxide in the form of nanocrystals to form a rigid-tough interpenetrating structure, which significantly improves the crack resistance of inorganic coating.
[0034] Based on the above embodiments, the mass of the carbonate-based phosphate dynamic anchoring layer is 1.0%-2.5% of the matrix mass. One end of the modifier molecule in the carbonate-based phosphate dynamic anchoring layer is combined with the Al2O3-SiO2 blend layer through the phosphate group, and the other end is molecularly compatible with the polycarbonate chain segment through the carbonate structure. At the same time, the surface hydroxyl groups are efficiently sealed, so that the moisture content of the finished product is ≤0.12%.
[0035] In some specific embodiments, the titanium dioxide particle size is 0.20~0.25μm. Under processing conditions of 280~320℃, it can significantly inhibit the yellowing and mechanical property degradation of polycarbonate, resulting in a yellowing index b-value ≤1.2 and a cantilever beam impact strength ≥70kJ / m. 2 .
[0036] This invention also provides a method for preparing titanium dioxide for high-temperature processing of polycarbonate, comprising the following steps: S1. Prepare a slurry with a solid content of 30%~40% by preparing rutile titanium dioxide, add sodium polyacrylate and polyethylene glycol-polypropylene glycol block copolymer as a composite dispersant, adjust the pH to 7.5~9.0, disperse at high speed and then heat to 65~75℃; S2. Add zirconium source solution to the slurry. When the zirconium source is added to 50% of the total amount, mix the high-valence metal source with the zirconium source in proportion and continue to add it. Keep it warm and mature to form a high-valence metal-zirconium composite defect passivation layer. S3. Gradually adjust the dropping rate of the zirconium source and aluminum source to make the system continuously transition from zirconium-rich to aluminum-rich. Then adjust the pH to 7.0~8.0 and adjust the dropping rate of the aluminum source and silicon source to make the system continuously transition from aluminum-rich to silicon-rich, forming a zirconium-aluminum-silicon continuous gradient dense layer. S4. Maintain a high flow rate of silicon source and add it in conjunction with a low flow rate of aluminum source, while adding tetraethyl orthosilicate to promote the formation of the outermost Al2O3-SiO2 blend layer. S5. Wash the slurry until the conductivity is ≤40μS / cm, and filter to obtain filter cake; S6. The filter cake is redispersed, heated, and carbonate-based phosphate ester is added. Dynamic anchoring is completed by reacting within a preset temperature range. The preset temperature range can be between 85-100°C. In some embodiments, the reaction within the preset temperature range includes reacting sequentially in at least three temperature stages, namely 88-92°C, 96-100°C, and 86-90°C (e.g., using a three-stage temperature control of 90-98-88°C). S7. After three-stage vacuum drying, inert airflow pulverization, and low-temperature dehumidification, a titanium dioxide product with a moisture content of ≤0.12% is obtained.
[0037] In some specific embodiments, the high-valence metal source is one or more of Sb2O5 and Nb2O5.
[0038] This invention addresses the problems of thermo-oxidative degradation, accelerated yellowing, and decreased mechanical properties that easily occur in polycarbonate during high-temperature melting and processing at 280-320℃. It provides a special titanium dioxide suitable for high-temperature polycarbonate processing and its preparation method, belonging to the field of inorganic pigment surface modification technology. The titanium dioxide uses rutile titanium dioxide as a matrix. From the inside out, the matrix surface includes a high-valence metal-zirconium composite defect passivation layer, a zirconium-aluminum-silicon continuously gradient dense layer (the outermost layer being an Al2O3-SiO2 blend layer), and a carbonate-based phosphate anchoring layer. Each layer has no obvious interfaces and exhibits a continuous transition structure. This invention reduces thermocatalytic activity through defect passivation, improves high-temperature crack resistance through gradient density and intermixed structures, and achieves low hygroscopicity and high compatibility through organic anchoring. The resulting special titanium dioxide has a water content of ≤0.12%, which can significantly inhibit the yellowing and mechanical decay of polycarbonate at 280~320 ℃. It is suitable for high-end polycarbonate materials of optical grade, automotive grade, and electronic and electrical grade. The preparation process is stable and controllable and can be directly adapted to industrial production lines.
[0039] The present application will be described in detail below through specific embodiments.
[0040] Example 1 Take 1000 g of chlorinated rutile titanium dioxide, add deionized water to disperse it into a slurry with a solid content of 33%, add sodium polyacrylate and polyethylene glycol-polypropylene glycol block copolymer as dispersants, adjust the pH to 8.2, disperse at high speed for 80 minutes, and heat to 70℃.
[0041] Zirconium oxychloride solution was added dropwise. When the zirconium source was halfway added, sodium fluoroantimonate solution was mixed with the zirconium source and the addition continued. After the addition was completed, the mixture was aged for 110 minutes to form a high-valence metal-zirconium composite defect passivation layer.
[0042] Subsequently, the zirconium source flow rate is gradually reduced and the aluminum source flow rate is increased to achieve a zirconium-aluminum gradient transition; then the pH is adjusted and the aluminum source flow rate is gradually reduced and the silicon source flow rate is increased to achieve an aluminum-silicon gradient transition, forming a zirconium-aluminum-silicon continuous gradient dense layer.
[0043] Maintaining a high flow rate of silicon source and co-dropping with a low flow rate of aluminum source, tetraethyl orthosilicate is added, and the reaction is carried out for 25 minutes, forming an Al2O3-SiO2 blend layer on the outermost layer of the inorganic coating.
[0044] Wash the slurry until the conductivity is ≤40 μS / cm, then filter it. After redispersing the filter cake, add carbonate-based phosphate ester and stir the mixture for 140 minutes under three temperature control conditions of 90-98-88 ℃.
[0045] Finally, after three-stage vacuum drying, nitrogen-protected pulverization, and low-temperature dehumidification, the finished product T1 with a moisture content of 0.11% was obtained.
[0046] Example 2 The difference from Example 1 is that the high-priced metal used is Sb. 5+ With Nb 5+ The mixture was compounded in a 1:1 ratio with a doping amount of 0.2%; the total amount of zirconium-aluminum-silicon gradient layer was increased; the amount of carbonate-based phosphate added was 2.2%; the remaining steps were the same, and the finished product T2 with a water content of 0.10% was obtained.
[0047] Example 3 The difference from Example 1 is that a sulfuric acid process rutile titanium dioxide substrate is used, the high-valence metal is doped with a single Nb2O5, the coating ratio is appropriately reduced, and the organic layer addition is 2.5%; the other steps are the same, and the finished product T3 with a water content of 0.12% is obtained.
[0048] Comparative Example 1 D1 was prepared by using traditional stepwise coating without composite passivation or intermixing coating, and by using ordinary silane modification, with all other conditions being the same.
[0049] Comparative Example 2 D2 was prepared without adding high-valence metal dopants, while keeping the rest of the structure and process unchanged.
[0050] Comparative Example 3 Without forming a blended coating layer, the outermost layer uses a traditional pure silicon outer layer to obtain D3.
[0051] Comparative Example 4 D4 was prepared by using a conventional one-step modification method instead of a three-stage dynamic anchoring method.
[0052] Performance testing: The titanium dioxide products obtained in the above embodiments and comparative examples were added to polycarbonate resin at a mass fraction of 10%, and then melt-blended at 300 °C for 10 min before injection molding to prepare standard test specimens. The performance of each test specimen was tested, and the results are as follows: The yellowing index (b) values of Examples T1, T2, and T3 are 1.1, 1.0, and 1.2, respectively, and their impact strengths are 70.5, 71.8, and 70.2 kJ / m, respectively. 2 The moisture content is ≤0.12%, and the coating layer is intact and without cracks.
[0053] The comparative example D1 had a yellowing index of 2.3 and an impact strength of 63.2 kJ / m. 2 Microcracks appeared in the coating; comparative examples D2, D3, and D4 were significantly inferior to the example in terms of yellowing, strength, moisture content, and coating integrity. Test results show that the present invention, through a multi-layered synergistic structure, achieves a unified effect of low-thermal catalysis, high coating stability, low moisture absorption, and high compatibility, exhibiting significantly superior performance compared to existing technologies.
[0054] The beneficial effects of implementing this invention include: (1) High-priced metal-zirconium composite defect passivation is adopted to reduce thermal catalytic activity from the source and significantly inhibit the high-temperature yellowing of polycarbonate.
[0055] (2) The continuous gradient dense layer + inorganic blend coating is used to eliminate interfacial stress and prevent cracking and peeling at high temperature and high shear.
[0056] (3) Dynamic anchoring with carbonate-based phosphate ester is adopted to achieve high sealing, low moisture absorption and high compatibility, and the finished product moisture content is ≤0.12%.
[0057] (4) The preparation process is continuous and stable, compatible with existing industrial production lines, and suitable for large-scale production.
[0058] The above are exemplary embodiments disclosed in this invention. The order of the disclosed embodiments is merely for descriptive purposes and does not represent the superiority or inferiority of the embodiments. However, it should be noted that the discussion of any of the above embodiments is merely exemplary and is not intended to imply that the scope of the disclosed embodiments of this invention (including the claims) is limited to these examples. Various changes and modifications can be made without departing from the scope defined by the claims. The functions, steps, and / or actions of the methods according to the disclosed embodiments described herein do not need to be performed in any particular order. Furthermore, although the elements disclosed in the embodiments of this invention may be described or claimed individually, they may be understood as multiple unless explicitly limited to a singular.
[0059] Those skilled in the art should understand that the discussion of any of the above embodiments is merely exemplary and is not intended to imply that the scope of the invention (including the claims) is limited to these examples. Within the framework of the invention, technical features of the above embodiments or different embodiments can be combined, and many other variations of the different aspects of the invention as described above exist, which are not provided in the details for the sake of brevity. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the invention should be included within the protection scope of the invention.
Claims
1. A titanium dioxide for high-temperature processing of polycarbonate, characterized in that, Using rutile titanium dioxide as a matrix, the surface of the matrix is coated with three structural layers from the inside to the outside. The three structural layers include a high-valence metal-zirconium composite defect passivation layer, a zirconium-aluminum-silicon continuous gradient dense layer, and a carbonate-based phosphate dynamic anchoring layer. The three structural layers are in a continuous transition state.
2. The titanium dioxide for high-temperature processing of polycarbonate according to claim 1, characterized in that, The high-valence metal-zirconium composite defect passivation layer is composed of one or two of ZrO2 and Sb2O5 and Nb2O5. The mass of ZrO2 is 0.5% to 1.0% of the mass of the matrix, and the doping amount of the high-valence metal is 0.1% to 0.2% of the mass of the matrix. Zirconium and the high-valence metal form a Zr-OM covalent bond structure, where M is Sb or Nb.
3. The titanium dioxide for high-temperature processing of polycarbonate according to claim 1, characterized in that, The zirconium-aluminum-silicon continuous gradient dense layer has an amorphous co-deposition structure, and its total mass is 1.5% to 3.5% of the matrix mass.
4. The titanium dioxide for high-temperature processing of polycarbonate according to claim 3, characterized in that, The zirconium-aluminum-silicon continuous gradient dense layer has a zirconium content that gradually decreases from the inside out, an aluminum content that first increases and then decreases, and a silicon content that gradually increases, with a coating density of 65% to 85%.
5. The titanium dioxide for high-temperature processing of polycarbonate according to claim 4, characterized in that, The outermost layer of the zirconium-aluminum-silicon continuous gradient dense layer is an Al2O3-SiO2 blend layer, wherein the mass of the Al2O3-SiO2 blend layer is 0.5% to 1.0% of the matrix mass, wherein the mass fraction of Al2O3 is 25% to 35% and the mass fraction of SiO2 is 65% to 75%.
6. The titanium dioxide for high-temperature processing of polycarbonate according to claim 5, characterized in that, In the Al2O3-SiO2 blend layer, Al2O3 is uniformly embedded in the amorphous network of silicon oxide in the form of nanocrystals, forming a rigid-tough interpenetrating structure.
7. The titanium dioxide for high-temperature processing of polycarbonate according to claim 5, characterized in that, The mass of the carbonate-based phosphate dynamic anchoring layer is 1.0%-2.5% of the matrix mass. One end of the modifier molecule in the carbonate-based phosphate dynamic anchoring layer is bonded to the Al2O3-SiO2 blend layer through the phosphate group, and the other end is molecularly compatible with the polycarbonate chain segment through the carbonate structure. At the same time, it achieves efficient sealing of surface hydroxyl groups, so that the moisture content of the finished product is ≤0.12%.
8. The titanium dioxide for high-temperature processing of polycarbonate according to claim 2, characterized in that, The titanium dioxide has a particle size of 0.20~0.25μm. Under processing conditions of 280~320℃, the resulting product has a yellowing index (b) ≤1.2 and a cantilever beam impact strength ≥70kJ / m². 2 .
9. A method for preparing titanium dioxide for high-temperature processing of polycarbonate, characterized in that, Includes the following steps: S1. Prepare a slurry with a solid content of 30%~40% by preparing rutile titanium dioxide, add sodium polyacrylate and polyethylene glycol-polypropylene glycol block copolymer as a composite dispersant, adjust the pH to 7.5~9.0, and then heat to 65~75℃ after dispersion. S2. Add zirconium source solution to the slurry. When the zirconium source is added to 40-60% of the total amount, mix the high-valence metal source with the zirconium source in proportion and continue to add it. Keep it warm and mature to form a high-valence metal-zirconium composite defect passivation layer. S3. Gradually adjust the dropping rate of the zirconium source and aluminum source to make the system continuously transition from zirconium-rich to aluminum-rich. Then adjust the pH to 7.0~8.0 and adjust the dropping rate of the aluminum source and silicon source to make the system continuously transition from aluminum-rich to silicon-rich, forming a zirconium-aluminum-silicon continuous gradient dense layer. S4. Maintain the addition of silicon source and co-add aluminum source, while adding tetraethyl orthosilicate to promote the formation of the outermost Al2O3-SiO2 blend layer; S5. Wash the slurry until the conductivity is ≤40μS / cm, and filter to obtain filter cake; S6. Redisperse the filter cake, heat it up and add carbonate-based phosphate ester, and react within the preset temperature range to complete the dynamic anchoring. S7. After vacuum drying, inert air pulverization, and dehumidification, a titanium dioxide product with a water content of ≤0.12% is obtained.
10. The method for preparing titanium dioxide for high-temperature processing of polycarbonate according to claim 9, characterized in that, The high-valence metal source is one or more of Sb2O5 and Nb2O5.
Citation Information
Patent Citations
Inorganic coating method for titanium dioxide
CN103214880A
Preparation method of special titanium dioxide pigment for polycarbonate
CN107805321A
Special titanium dioxide for polycarbonate and preparation method thereof
CN114231054A
High-temperature-cooking-resistant and good-processability PC material as well as preparation method and application thereof
CN114634694A